Formation of oil and gas reservoirs in deep water areas of the South Caspian Depression - Gahraman Nariman Ogly Gahramanov (Earth Sciences Research Journal)
The aim of the article is the identification and characterization of complex factors acting simultaneously on forming a large-sized reservoirs in the deep South Caspian Basin, as well as the formation of a model based on a combination of causing the formation of hydrocarbon deposits synchronously occurring natural processes. The article comments on reasons for high layer pressures existing in the fields located in the South Caspian Depression (SCD), studies impacting factors and develops a methodical estimation on this basis. The tectonic factor and density-barometric model can become the main criterion for selection of priority projects for exploration, site selection for drilling and to accommodate exploration and production wells. Obtained results allow conducting effective studies of the exploration and development of oil and gas condensate fields in the SCD area.